2017
DOI: 10.1186/s12916-017-0916-3
|View full text |Cite
|
Sign up to set email alerts
|

The renin–angiotensin system: a possible new target for depression

Abstract: Depression remains a debilitating condition with an uncertain aetiology. Recently, attention has been given to the renin–angiotensin system. In the central nervous system, angiotensin II may be important in multiple pathways related to neurodevelopment and regulation of the stress response. Studies of drugs targeting the renin–angiotensin system have yielded promising results. Here, we review the potential beneficial effects of angiotensin blockers in depression and their mechanisms of action. Drugs blocking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 220 publications
(192 reference statements)
1
115
2
1
Order By: Relevance
“…Examples include statins, aspirin and angiotensin antagonists 788, 789, 790, 791, 792, 793. The implications are that clinicians should be actively engaged in the management of these disorders, and should select therapies from those agents that may have benefit in mood symptoms.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Examples include statins, aspirin and angiotensin antagonists 788, 789, 790, 791, 792, 793. The implications are that clinicians should be actively engaged in the management of these disorders, and should select therapies from those agents that may have benefit in mood symptoms.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Clinical data, although not as yet double-blind trials, have suggested that drugs, such as anti-hypertensive drugs that block the production of Angiotensin II, help mood disorders and produce a positive outcome in animal models of depression. It has been proposed that aldosterone has a role in depression [33][34][35], and that the level of this hormone predicts the outcome of the disorder [36]. Therefore, future research should monitor the levels of hormones associated with the renin-angiotensin-aldosterone system, and relate these to psychological functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that the RAA system may be involved in the pathophysiology of MDD and be a potential target for depression treatment . Diverse studies have found that neuroimaging alterations in MDD were associated with angiotensin‐converting enzyme insertion/deletion (ACE I/D) and type 1 angiotensin II receptor (AGTR1) genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that the RAA system may be involved in the pathophysiology of MDD and be a potential target for depression treatment. 109,110 Diverse studies have found that neuroimaging alterations in MDD were associated with angiotensin-converting enzyme insertion/deletion (ACE I/D) and type 1 angiotensin II receptor (AGTR1) genes. ACE-D carriers showed significantly smaller anterior cingulate gyrus volumes and larger middle temporal gyrus volumes, 46 as well as decreased default-mode network activity in remitted geriatric depression.…”
Section: Association Of Ras System-related Genes With Neuroimagingmentioning
confidence: 99%